Allusion in Steinbeck’s The Grapes of Wrath - TALHA Ilham; Zeghdi salah (University of Eloued جامعة الوادي, 2025)
الملخص: رواية "عِنَبُ الغَضَبِ" (1939) لجون ستاينبك تستند إلى مرجعية نصية ثرية لبحث الظلم الاجتماعي، وتسعى من وجْهٍ ما إلى إضفاء الطابع الإنساني على محنَةِ أتباعِ حقبة "الغُبار". تبحث هذه الدراسة كيف تُستحضَرُ الإشاراتُ إلى الكتاب المقدس، والتاريخ، والأساطير كأدوات سردية وفكرية تُعزِّزُ موضوعات القهر، والنضال، والتعاون في الرواية. اعتمد هذا البحث منهجَ التحليل النصي النوعي مسترشدًا بتصنيف "ليبيهالم" (1997)، حيث تم تحديد الاستراتيجية التلميحية وتفسيرها عبر القراءة المتأنية.كشفت الدراسة أن التلميحات الكتابية ترفع رحلة عائلة "جود" إلى مستوى الامتحان الروحي، بينما تغرِسُ التلميحات التاريخية معاناةَ العائلة بقوة في سياق الكساد العظيم الاجتماعي-الاقتصادي، في حين تعكسُ الثيماتُ الأسطوريةُ محنتَهم كأنماطٍ بدئيةٍ للمقاومة. فضلًا عن ذلك، وظّفَ ستاينبك التلميحَ عمدًا لتعزيز الأثر العاطفي للرواية، وشحذِ نقده لرأسمالية عبر تحويل الإيمان من صبرٍ إلى نداءٍ للتضامن. من محدوديات البحث ذاتيةُ تحديد التلميحات المحتملة الغموض، وتباينُ معرفة القارئ بالسياقات الثقافية المرجعية. تؤكد هذه الدراسة الأهمية الخالدة لـ"عِنَبِ الغضب"، وتكشف كيف يستخدم الأدبُ التناصَّ والعدسةَ النصيةَ لربط النضالات التاريخية والمعاصرة من أجل العدالة. Summary: John Steinbeck's The Grapes of Wrath (1939) draws on rich intertextual reference to discuss social injustice and in some way to humanize the plight of devotees of the Dust Bowl. This research examines how allusions to the Bible, history, and myth are used as narrative and ideological devices that augment the themes of oppression, struggle and cooperation in the novel. This research employs a qualitative textual analysis approach that uses Leppihalme's (1997) classification as guidance and close reading as an illusive strategy for identification and interpretation of allusion . This study discovered that biblical allusions elevates Joads’ journey to spiritual trial, whereas historical allusions firmly embed the Joads’ suffering within the socioeconomic context of the Great Depression, while the use of mythological motifs universally reflects their plight as archetypes of resistance. In addition, Steinbeck purposefully used allusion to heighten emotional impact of the novel, and sharpen the critique of capitalism by reframing faith from endurance to plea for solidarity. The potential limitations of this analysis are the subjective nature of identifying potentially ambiguous allusion, and the varied contextual knowledge of the readers’ cultural references. This investigation emphasizes the lasting significance of The Grapes of Wrath, and demonstrates how literature uses intertextuality and intertextual lens to create links between historical and contemporary struggles for justice.
Master's Degree In Literature and Civilization
Keywords: عِنَبُ الغضب، التلميح، جون ستاينبك، الكساد العظيم.; The Grapes of Wrath; allusion; John Steinbeck; Great Depression.